Presentation of concurrent thrombotic thrombocytopenic purpura and Graves' disease. Issue 7 (22nd October 2022) - Casasanta, Nicole A.; Shah, Nirali; Troy, Kevin; Edwards, Colleen; Patel, Rima B.
Abstract : Thrombotic thrombocytopenic purpura (TTP) is a type of thrombotic microangiopathy caused by deficient activity of ADAMTS13 that most commonly occurs secondary to an acquired autoantibody. There are limited data on the association between TTP and autoimmune thyroid disease. We present a case of acquired TTP in the setting of thyrotoxicosis from Graves' disease. Our patient improved with standard treatment of both TTP and thyrotoxicosis. A retrospective review of patients with TTP at our institution demonstrated that 32% had another autoimmune disorder, highlighting the concept of polyautoimmunity. These findings suggest an association between TTP and uncontrolled autoimmune disease. In patients with newly diagnosed TTP, physicians should evaluate for other autoimmune diseases and check thyroid function tests.